Specializing Context-Free Grammars with a (1 + 1)-EA - Manzoni, Luca (2022)
Manzoni, L., Bartoli, A., Castelli, M., Goncalves, I., & Medvet, E. (2020). Specializing Context-Free Grammars with a (1 + 1)-EA. IEEE Transactions on Evolutionary Computation, 24(5), 960-973. [9047973]. https://doi.org/10.1109/TEVC.2020.2983664